100% renewable electricity policies in U.S. cities: A mixed methods analysis of adoption and implementation. (August 2022) - Kunkel, Leah C.; Breetz, Hanna L.; Abbott, Joshua K.
Abstract: Since 2016, over 180 US cities have committed to 100% renewable electricity (100RE). This paper uses a two-stage, mixed methods approach to examine adoption and implementation of these ambitious new policies, highlighting that many cities will need new institutions and administrative capacities for successful implementation. We first conduct a multivariate regression to examine demographic, institutional, and policy factors in 100RE adoption. Although adoption is correlated with prior municipal and green energy policies, adopting cities are no more likely to have key institutional resources to support implementation, such as locally controlled utilities, sustainability staff, or city managers. An unexpected correlation with poverty rates raises further questions about potential policy costs and the importance of developing financial and administrative capacity for policy design. To examine how cities are addressing these challenges, we subsequently conduct case studies of implementation in six states. We find that cities in different states are pursuing markedly different implementation pathways, showing that state-specific policies and networks shape how cities address institutional challenges. Although there are multiple approaches for implementation, successful 100RE commitments required institutional innovation, communication, and networking. Highlights: Analyzes adoption and implementation of cities' 100% renewable energy (100RE) goals. Population, education, and green energy policies are correlated with adoption. Less wealthy populations are unexpectedly correlated with adoption. Sustainability staff and locally controlled utilities do not predict 100RE adoption. Implementation depends on staffing, financial capacity, and energy jurisdiction.